PERAN ULAMA DAYAH PADA PEMBINAAN MODERASI BERAGAMA DI DAERAH PERBATASAN ACEH-SUMUT (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2023)
The important role of Dayah ulama in fostering religious moderation is very necessary, especially for communities on the Aceh-North Sumatra border. This is because Dayah ulama have quite a large influence on religious activities in society. Therefore, this research aims to determine the role of Dayah ulama and the obstacles faced in fostering religious moderation in communities in the Aceh-North Sumatra border area. This research uses a qualitative method where the researcher goes directly to the research location, then the data from the analysis is presented and discussed using data collection techniques through observation, interviews, and documentation. The results of the research show that the role of ulama in fostering religious moderation on the Aceh-North Sumatra border is as advisors, counselors, reminders, and coolants to the community when there is friction between communities and also as a calmer when there is disharmony. Ulama also fosters and guides people's religious behavior. In fostering people's religious behavior, ulama refer to the Al-Quran, hadith, and the books they master. Meanwhile, the obstacles faced are the lack of public understanding of an adequate understanding of religion and also the lack of willingness of some people to take part in and attend Islamic studies such as majlis taklim filled by Dayah ulama, so that with minimal knowledge, the community does not understand how to be a true Muslim and how to respect it. Others include a lack of understanding about tolerance with followers of other religions.